Organophosphate esters in biota, water, and air from an agricultural area of Chongqing, western China: Concentrations, composition profiles, partition and human exposure - He, Ming-Jing; Lu, Jun-Feng; Wei, Shi-Qiang (Environmental pollution (1987), 2019)
We measured the concentrations of organophosphate esters (OPEs) in some biotic samples which can serve as human foodstuffs and ambient environments including air and river water from an agricultural area of Chongqing, western China. Fish samples exhibited highest OPEs levels (960 ng/g lipid weight) among the biota, followed by chicken (676 ng/g lw), cattle (545 ng/g lw) and pigs (535 ng/g lw). Tributyl phosphate (TNBP), tris (2-methylpropyl) (TIBP) and chlorinated OPEs were the major analogs in biotic samples, which appeared similar with the patterns from river water and outdoor air, but apparently different from indoor air. To further investigate the influence of ambient environment on the distribution of OPEs in biota, we analyzed the correlation between OPEs concentrations in ambient environment and biological samples, and the results revealed that most of the samples (except for pig samples) heavily correlated with outdoor air, whereas only fish and cattle samples were strongly correlated with river water. The partitioning behaviors of OPEs among biota, air and river water were also studied through calculating the biota-water accumulation factors (BWAFs), biota-air accumulation factors (BAAFs) and air-water partitioning factor (AWPFs). Significantly linear correlations (P < 0.05) were observed between log (BWAFs) and log (KOW) values, and between log (AWPFs) and log H (Henry's law constants), nevertheless log (BAAFs) was increasing along with the log (KOA) values. The daily intake (DI) values were estimated via foodstuffs ingestion and environmental exposure. The estimated DI values of OPEs from food and ambient environments were 1.78 ng/kg-bw/day, 1.23 ng/kg-bw/day and 1.42 ng/kg-bw/day in toddlers, children and adults, respectively, which lay at the low end of the reported data and well below the reference dose (RfD). [Display omitted] •Organophosphate esters (OPEs) were measured in biota and ambient environment.•Composition profiles of OPEs in biota were similar with those in ambient environment.•The partitioning behaviors of OPEs were investigated among biota, air and river water.•Environmental exposure was the major contributor for human exposure to OPEs compared with food ingestion. Similar congener patterns of OPEs were demonstrated between the biological samples and ambient environment. The DI values were estimated via foodstuffs ingestion and environmental exposure.